(untitled) (European Journal of Pure and Applied Mathematics, 2018)
The aim of this manuscript is to present a unique common fixed point theorem for six mappings satisfying (φ ,ψ )-contractions using (E.A) property in the framework of G_b- metric spaces. An illustrative example is also given to justify the established result.